Clinical and Demographic Profile of Chronic Pancreatitis: A Retrospective Study in Bangladesh (Medicine Today, 2025)
Introduction: Chronic pancreatitis is characterized by irreversible damage to the pancreas that leads to pain and/or exocrine and endocrine insufficiency. In this study, we investigated the demographic profile, clinical feature and therapeutic modalities of chronic pancreatitis in Bangladesh. Materials and Methods: This is a retrospective hospital-based study. All patients admitted with chronic pancreatitis in Gastroenterology department of two tertiary care hospitals from Jan. 2019 to Dec.2022 were included in this study. Results: A total of (n=106) patients were enrolled in this study with a median age of 17.67 ±15.47 years. Abdominal pain was a presenting symptom in most of the cases (89.6%). Forty-two patients (39.6 %) had diabetes mellitus. Ductal dilatation (48.11 %) and pancreatic calcification (51.89 %) were the most common ultrasonological findings. All the patients were receiving medical treatment. Two patients undergone pancreato-jejunostomy & nine patients (8.5 %) received endo therapy. Out of complications, seven patients (6.6 %) had evidence of pseudocyst, six patients (5.66%) had biliary obstruction & four patients (3.77%) had ascites. Conclusion: In this study, idiopathic chronic pancreatitis (CP) was observed as the most common & should be treated by multidisciplinary team.Medicine Today 2025, Vol.37 (1): 1-4